ASIC3 plays a protective role in delayed-onset muscle soreness (DOMS) through muscle acid sensation during exercise - Khataei, Tahsin; Benson, Christopher J. (Frontiers in Pain Research, 2023)
Immediate exercise-induced pain (IEIP) and DOMS are two types of exercise-induced muscle pain and can act as barriers to exercise. The burning sensation of IEIP occurs during and immediately after intensive exercise, whereas the soreness of DOMS occurs later. Acid-sensing ion channels (ASICs) within muscle afferents are activated by H+ and other chemicals and have been shown to play a role in various chronic muscle pain conditions. Here, we further defined the role of ASICs in IEIP, and also tested if ASIC3 is required for DOMS. After undergoing exhaustive treadmill exercise, exercise-induced muscle pain was assessed in wild-type (WT) and ASIC3−/− mice at baseline via muscle withdrawal threshold (MWT), immediately, and 24 h after exercise. Locomotor movement, grip strength, and repeat exercise performance were tested at baseline and 24 h after exercise to evaluate DOMS. We found that ASIC3−/− had similar baseline muscle pain, locomotor activity, grip strength, and exercise performance as WT mice. WT showed diminished MWT immediately after exercise indicating they developed IEIP, but ASIC3−/− mice did not. At 24 h after baseline exercise, both ASIC3−/− and WT had similarly lower MWT and grip strength, however, ASIC3−/− displayed significantly lower locomotor activity and repeat exercise performance at 24 h time points compared to WT. In addition, ASIC3−/− mice had higher muscle injury as measured by serum lactate dehydrogenase and creatine kinase levels at 24 h after exercise. These results show that ASIC3 is required for IEIP, but not DOMS, and in fact might play a protective role to prevent muscle injury associated with strenuous exercise.